1998
DOI: 10.1542/peds.101.3.e7
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental/Neuroradiologic Recovery of a Child Infected With HIV After Treatment With Combination Antiretroviral Therapy Using the HIV-Specific Protease Inhibitor Ritonavir

Abstract: An 8-year, 2-month-old African-American boy was infected with HIV through vertical transmission. Regular monitoring of the patient's neurodevelopmental status has been conducted as part of his participation in longitudinal research protocols. For the first 51/2 years of life, his neurodevelopmental status was normal, with cognitive functioning as measured by standardized psychometric tools solidly in the average range. Speech and language skills were age-appropriate. Tests of gross and fine motor functioning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 13 publications
(13 reference statements)
0
13
0
Order By: Relevance
“…After 12 weeks of antiretroviral therapy that decreased viral burden and associated inflammatory markers in the plasma and cerebrospinal fluid (CSF), her performance on cognitive and motor testing had dramatically improved and most but not all of her presenting deficits were reversed. Similar clinical recovery, accompanied by reversal of radiologic signs of cerebral atrophy, was reported after antiretroviral therapy in an HIV-1-infected child with language, attention, and motor deficits that had caused him to lose developmental milestones and prevented him from communicating with others at school and at home (Tepper et al 1998). Cohort studies following patients beginning highly active antiretroviral therapy (HAART) provide further evidence of a large reversible component in HAD (Thurnher et al 2000;Ferrando et al 2003).…”
Section: Introductionmentioning
confidence: 69%
“…After 12 weeks of antiretroviral therapy that decreased viral burden and associated inflammatory markers in the plasma and cerebrospinal fluid (CSF), her performance on cognitive and motor testing had dramatically improved and most but not all of her presenting deficits were reversed. Similar clinical recovery, accompanied by reversal of radiologic signs of cerebral atrophy, was reported after antiretroviral therapy in an HIV-1-infected child with language, attention, and motor deficits that had caused him to lose developmental milestones and prevented him from communicating with others at school and at home (Tepper et al 1998). Cohort studies following patients beginning highly active antiretroviral therapy (HAART) provide further evidence of a large reversible component in HAD (Thurnher et al 2000;Ferrando et al 2003).…”
Section: Introductionmentioning
confidence: 69%
“…9 In addition, McCoig et al observed that children infected with HIV who were on combination anti-retroviral therapies showed a significant decline in neurologic abnormalities, as well as viral load (VL), throughout the course of treatment. 10 Nevertheless, the incidence of PHE and the clinical manifestations of PHE have not been systematically assessed since the introduction of HAART.…”
mentioning
confidence: 99%
“…This supposition is based on neuropathologic data obtained from patients in the pre-HAART era, but is buttressed by reports of adult and pediatric patients with HIV-1 and neurologic disease that experienced substantial improvement in both neuropsychologic and neuroradiologic indices (Gendelman et al 1998;Tepper et al 1998). Further support for antiviral amelioration of neurologic disease associated with lentiviral infection can be garnered from studies by Fox et al (2000) using SIV-infected rhesus macaques, where the authors have demonstrated that treatment with PMPA ameliorates neuropsychological deficits and normalizes sensory-evoked potentials (SEPs), a measure of the integrity of brainstem polysynaptic pathways in response to an event-related stimulus (such as light, sound, or recognition of a singular event in a stimulation pattern), but does not reverse motor deficits.…”
mentioning
confidence: 99%